Cover Feature: Chemo‐Biological Upcycling of Poly(ethylene terephthalate) to Multifunctional Coating Materials (ChemSusChem 19/2021). Issue 19 (15th September 2021) - Kim, Hee Taek; Hee Ryu, Mi; Jung, Ye Jean; Lim, Sooyoung; Song, Hye Min; Park, Jeyoung; Hwang, Sung Yeon; Lee, Hoe‐Suk; Yeon, Young Joo; Sung, Bong Hyun; Bornscheuer, Uwe T.; Park, Si Jae; et al.
Abstract : The Cover Feature shows a direct chemo‐biological upcycling of poly(ethylene terephthalate) (PET) into a functional coating agent through a combination of chemo‐enzymatic depolymerization and biotransformation. More information can be found in the Full Paper by H. T. Kim, M. H. Ryu, et al .